(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Pedagogical possibilities of developing professional competences of future teachers based on innovative educational technologies, pedagogical and psychological conditions of organizing educational classes in the educational environment, we can see in this article. All students in the audience are guaranteed to master their abilities. The student’s mastery and ability to use the acquired knowledge in everyday life and practical activities is determined by the level of skills and qualifications. If the professor-teacher learns to work with students on the basis of interactive methods and can bring it into their educational activities, all students will achieve almost the same results.Independent activity serves to implement the formation of knowledge, skills and competencies specified in the curriculum of a particular subject and required to be mastered by the student, and is carried out in the classroom or outside the classroom on the basis of the advice and recommendations of the teacher. Due to the specifics of the subject, various types of independent learning are being developed. Independent learning and control in the education system are considered one of the main factors of independent learning. In independent learning, it is necessary, first of all, to form in students the need for independent learning, free, creative activity, and most importantly, independent thinking. The establishment of systematic work on the implementation of the independent learning process in higher educational institutions, training students to work independently, will be the basis for training a new generation of creative and socially active, capable of independently finding their place in socio-political life, capable of setting and solving promising tasks. Therefore, this article attempts to reveal the pedagogical and psychological problems of modern forms used in organizing students’ independent work and ways to solve them.